Kajian Daya Dukung Lingkungan Berbasis Ketersediaan dan Kebutuhan Air di Ibu Kota Nusantara - Amru, Khaerul; Anjani, Raissa; Plamonia, Nicco; Dewa, Riardi Pratista (BRIN Publishing (Penerbit BRIN), 2025)
The relocation of the capital of Indonesia from Jakarta to the capital of the archipelago (IKN) has an impact on increasing the population. This increase in population is directly proportional to the increase in the need for clean water. This study aims to determine the carrying capacity of the IKN environment as the capital of a new country based on water availability and needs. The study was conducted by combining quantitative descriptive analysis by comparing the volume of water availability with community needs which results were then classified into water carrying capacity classes. Based on the calculation results, the estimated volume of water available at IKN reaches 712,020,738.75 m3 / year. With water needs for the community reaching 314,505,600.00 m3 / year, the value of water carrying capacity is 2.26 and is included in the category of conditional safe. The volume of water available at IKN is stated to be still able to meet the needs of the community. However, various efforts are needed to maintain the quantity and quality so as to meet the needs of the community in the long run.